Teheran, Iran. Das Projekt TehranDigital der Außenstelle Teheran: ›Nur‹ Digitalisierung? - Thomalsky, Judith (e-Forschungsberichte des DAI, 2020)
Since 2015 is the archive of the Tehran Branch »under digitalization«. Approx. 50.000 documents are already settled in our database and linked to iDAI.objects/Arachne. Beside the online-access of comprehensive 100 years of archaeological documentation in Iran that is stored in our archive and photograph collection, one major concern is the consolidation of our data with the different archives of the Iranian cultural heritage institutions which again provides important and innovative perspectives for future archaeological research and management of the Cultural Heritage of and in Iran.